PREDICTING FIRE BEHAVIOR IN HERBACEOUS FUEL COMPLEX AT DOI ANGKHANG, CHIANGMAI PROVINCE - Kaitpraneet, San; Thaiutsa, Bunvong (วารสารวนศาสตร์ไทย, 2022)
Predicting fire behavior in herbaceous fuel complex was conducted in Summer, 1983 at Doi Angkhang, Fang District, Chiangmai Province, in order to construct fuel model for herbaceous fuel complex and to predict fire behavior in the herbaceous fuel complex at Doi Angkhang using Rothermel’s fire spread model. The herbaceous fuel complex was characterized and variables were adjusted for use in Rothermel’s (1972) spread model. The fire behavior predictions were attempted in various conditions of wind speeds ranged from 0 to 10 miles per hour, slopes ranged from 0 to 40 percent, and fuel moisture contents ranged from 6 to 20 percent. The program outputs were predicted rates of fire spread ranged from 0.022 to 2.978 meters per second, the predicted fire line intensities ranged from 491.121 to 97971.762 kilowatts per meter, and the predicted flame lengths ranged from 1.34 to 15.33 meters. Two experimental fires were conducted to test against the predicted fire behaviors. The predicted values of fire line intensities and flame lengths were closely agreed with the observed values, except, the predicted rate of fire spread was five times less than the observed value, it might be due to wind speed was not measured at the time of burning. However, the predicted values of rate of fire spread are more reasonable to the given ranges of wind speed, thus, the information of this study still be useful in fire management planning and in land use planning.